Highly asymmetric structure : synthesis of gold nanobroom (aunb). - Lee, Siow Wai. (2010)
For recent years, breaking the symmetry of nanoparticles (NPs) has attracted much interest from the researchers due to its potential applications to make nanodevice and unique properties. The mechanism, however, is not clearly understood yet. Here, we reported the use of gold nanorods (AuNRs) to synthesize gold nanobroom (AuNB), which is asymmetric. By using nanobroom, a complex nanodevice that cannot be produced merely by symmetric building block, may be produced. Controlled experiments were done using long AuNRs (175nm) and short AuNRs (45nm) resulted in the former produced and latter non-produced of the nanobroom. All the structures were analyzed using near infra red (NIR) spectroscopy, Raman spectroscopy and transmission electron microscopy (TEM).